Revealing the scenario of facilities management and maintenance in Malaysia: a systematic review / Syarifah Nur Shaqina Syed Shabahar, Haryati Mohd Isa and Nor Suzila Lop - Syed Shabahar, Syarifah Nur Shaqina; Mohd Isa, Haryati; Lop, Nor Suzila (Universiti Teknologi MARA, Perak, 2024)
The field of Facilities Management and Maintenance (FMM) in Malaysia has undergone substantial evolution and transformation. Despite abundant research on FMM practices, conducting a systematic review on this issue has proven challenging due to the lack of review procedures. This poses a significant barrier for researchers to replicate or interpret the findings. Hence, this research aims to conduct a systematic literature review of the current FMM practices in Malaysia. The review processes comprised five key methodological steps, namely review, formulation of research questions, systematic searching strategies based on identification, screening, and eligibility on various established databases such as Scopus, Web of Science, Science Direct, and Google Scholar. This is then followed by quality appraisal, as well as data extraction and analysis. Four primary themes were identified based on the thematic analyses: (1) FMM evolution; (2) the current state of FMM; (3) technology; and (4) policy and regulation. These four themes were then divided into nine sub-themes. Findings show that despite the progress, FMM still faces challenges, particularly in standardizing the maintenance process, which impacts on overall service quality.